Identifying the Genetic Population Structure Knowledge Gaps Hindering an Improved Management of the Spurdog (Squalus acanthias) stock in the Northeast Atlantic: A Systematic Review - Mascareño Suárez, Francisco (UiT The Arctic University of Norway, 2022)
Despite its long history of exploitation, there is limited information about the spurdog. Therefore, it is important to identify which general and genetic information is available for the species and what is missing to resolve stock structure and advice future management schemes. The goal of this study was to identify the knowledge gaps, in terms of genetic population structure and diversity, which could inform an improved fisheries management for the spurdog in the Northeast Atlantic Ocean and Mediterranean Sea. To achieve this, a systematic review and a series of phylogenetic analyses using the NADH2 marker were done. Results from the review showed there is very limited general information about the species in the study regions, with only 38 documents found out of over 6000 hits. Only 3 studies were found concerning its genetic structure and diversity, with high diversity found for all studies but no genetic differentiation, except for the subpopulation in the Adriatic Sea. No genetic structure was found for the species in the Northeast Atlantic, but fine structuring was found for the Mediterranean Sea, indicating different stocks. The phylogenetic trees showed complex taxonomical relationships within the Squalus genus and no clear formation of monophyletic clades according to the location in which the samples were taken for sequences of S. acanthias. Major conclusions indicate the need for collecting more information, particularly with less invasive methods, given the zero TAC in the areas and the limitations of fisheries surveys, as well as more sampling efforts in regions different from Norway, the United Kingdom, and the Adriatic Sea. Furthermore, given that the phylogenetic analysis of the species with the NADH2 marker was inconclusive, the use of more efficient genetic markers, such as microsatellites or single nucleotide polymorphisms, is recommended for identifying fine genetic structuring in the populations.